Multi-agent hybrid mechanism for financial risk management - Jianyuan Yan; Jui-Jung Liao; Ching-Hui Shih (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The goal of this study was to propose the multi-agent mechanism to forecast the corporate financial distress. Design/methodology/approach: This study utilized numerous methods, namely random subspace method, discriminant analysis and decision tree to construct the multi-agent forecasting model. Findings and Originality/value: The study shows a superior forecasting performance. Originality/value: The use of multi-agent model to predict the corporate financial distress.
Keywords: 650; hybrid model; multi-agent mechanism; financial distress; intangible assets; risk management